The nuclear receptor LRH-1 critically regulates extra-adrenal glucocorticoid synthesis in the intestine - Mueller, Matthias (The Rockefeller University Press, 2006)
The nuclear receptor liver receptor homologue-1 (LRH-1, NR5A2) is a crucial transcriptional regulator of many metabolic pathways. In addition, LRH-1 is expressed in intestinal crypt cells where it regulates the epithelial cell renewal and contributes to tumorigenesis through the induction of cell cycle proteins. We have recently identified the intestinal epithelium as an important extra-adrenal source of immunoregulatory glucocorticoids. We show here that LRH-1 promotes the expression of the steroidogenic enzymes and the synthesis of corticosterone in murine intestinal epithelial cells in vitro. Interestingly, LRH-1 is also essential for intestinal glucocorticoid synthesis in vivo, as LRH-1 haplo-insufficiency strongly reduces the intestinal expression of steroidogenic enzymes and glucocorticoid synthesis upon immunological stress. These results demonstrate for the first time a novel role for LRH-1 in the regulation of intestinal glucocorticoid synthesis and propose LRH-1 as an important regulator of intestinal tissue integrity and immune homeostasis.